Desenvolvimento de um sistema de manobras de seccionadores de alta tensão visando seu processo de automação - Rocha, Luciano Favretto da (2014)
Currently the process of operation of breakers remotely has been a problem for companies operating within the national electric system, always requiring the supervision of a local operator to ensure the success of the operation. This work presents a proposal to solve this issue by presenting some changes to the original design disconnectors type DA. To assess the efficiency of the proposed some tests and tests in full scale prototype were performed using a double disconnector opening under various operating conditions. A directional motovibrator adjusted in frequency 87Hz was used in order to reduce the strength of dry friction between the moving parts to provide proper connection of the main contacts, in addition to relieving the residual stresses of the mechanical closure mechanisms. A laser is used to inform the center of the operating state of the connection.